2011
DOI: 10.4047/jap.2011.3.3.136
|View full text |Cite
|
Sign up to set email alerts
|

Flexural properties of a light-cure and a self-cure denture base materials compared to conventional alternatives

Abstract: PURPOSEA new light curing urethane dimethacrylate and a cold curing resin with simpler and faster laboratory procedures may have even improved flexural properties. This study investigated the 3-point flexural strengths and flexural moduli of two alternate base materials.MATERIALS AND METHODSA cold curing resin (Weropress) and a light curing urethane dimethacrylate base material (Eclipse). Along with Eclipse and Weropress, a high impact resin (Lucitone199) and three conventional base materials (QC 20, Meliodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
(19 reference statements)
2
12
0
Order By: Relevance
“…This increase could be attributed to high amount of residual monomer which acts as plasticizer which reduce the polymer inter-chain forces and reduce the glass transition temperature which render the resin softer and more flexible (28). Our finding was in agreement with Mumcu et al (29) in 2011.…”
Section: Discussionsupporting
confidence: 94%
“…This increase could be attributed to high amount of residual monomer which acts as plasticizer which reduce the polymer inter-chain forces and reduce the glass transition temperature which render the resin softer and more flexible (28). Our finding was in agreement with Mumcu et al (29) in 2011.…”
Section: Discussionsupporting
confidence: 94%
“…19,20 Denture processing techniques have been developed to decrease these distortions while enhancing productivity of the dental laboratory. Previous studies 2,21,22 evaluated the flexural strength of denture base materials, and Eclipse showed the highest mean flexural strength values, which may be a useful alternative to conventional denture base resins. Those studies differed from the present study in the test method and materials evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…The prepared samples were randomly divided into four groups (n = 10). Based on previously published studies [27,28], effect size (d) 1.6, α at 0.05, and 1-β (power) at 0.9 the sample size was determined to be 10 per sub-group, resulting in a total of 40 specimens per group. The sample size was calculated with the G*Power software (version 3.1; University of Dusseldorf) [29].…”
Section: Preparation Of the Samplesmentioning
confidence: 99%